Pyrolysis of Microalgae Chlorella sp. using Activated Carbon as Catalyst for Biofuel Production - Viqhi Aswie; Lailatul Qadariyah; Mahfud Mahfud (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2021)
Microalgae, as a potential raw material for biofuel, has several advantages compared to other biomass. One effective way to convert microalgae into biofuel is by thermal cracking or pyrolysis, and using a catalyst or not. So far, studies on the use of microalgae, that are converted into biofuels, is still use highly concentrated catalysts in packed bed reactors, which is not economical. Therefore, the aim of this study is to convert Chlorella sp. into biofuels with conventional pyrolysis without and using an activated carbon catalyst using packed bed reactor with bubble column. The reaction temperature is 400–600 °C, pyrolysis time is 1–4 hours, and the active carbon catalyst concentration is 0–2%. The 200 grams of Chlorella sp. and the catalyst was mixed in a fixed bed reactor under vacuum (−3 mm H20) condition. Next, we set the reaction temperature. When the temperature was reached, the pyrolysis was begun. After certain time was reached, the pyrolysis produced a liquid oil product. Oil products are measured for density and viscosity. The results showed that the conventional pyrolysis succeeded in converting microalgae Chlorella sp. into liquid biofuels. The highest yield of total liquid oil is obtained 50.2 % (heavy fraction yield, 43.75% and light fraction yield, 6.44%) at the highest conditions which was obtained with 1% activated carbon at a temperature and pyrolysis time of 3 hours. Physical properties of liquid biofuel are density of 0.88 kg/m3 and viscosity of 5.79 cSt. This physical properties are within the range of the national biodiesel standard SNI 7182-2012. The packed bed reactor completed with bubble column is the best choice for converting biofuel from microalgae, because it gives different fractions, so that it is easier to process further to the commercial biofuel stage. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).